The Role of RDI and Technology Emphasis on Operation and Sales Performance that Implies Financial Performance - Fernandes, Maleakhi; Utomo, Prio; Purwanto, Sri (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
Competition among companies, particularly in the technology and telecommunications sectors, demands a high level of innovation to meet consumer needs. The use of advanced technology and investment in research and development (R&D) are expected to be key factors in creating a competitive advantage amid intense business competition. The use of narratives in corporate reports is also expected to build a positive image among stakeholders, foster trust, and attract market attention. This study aims to examine the effect of R&D intensity and technology emphasis on financial performance through the mediation of operational and sales performance in technology and telecommunications companies. The research gap identified is the limited number of studies related to R&D in technology and telecommunications companies, especially those utilizing a content analysis approach. The research uses panel data and is conducted on three technology and telecommunications companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The samples were selected using a purposive sampling method. The results show that technology emphasis and operational performance have a significant influence on a company’s financial performance, while the relationships among other variables were found to be insignificant. Therefore, companies are encouraged to strengthen their technology emphasis and operational efficiency to enhance productivity and improve financial performance.